2021
DOI: 10.1177/0954411921996565
|View full text |Cite
|
Sign up to set email alerts
|

A study on using expanded perlite with hydroxyapatite: Reinforced bio-composites

Abstract: People are exposed to different kinds of diseases or various accidents in life. Hydroxyapatite (HA) has been widely employed for bone treatment applications. In this study, HA was extracted from sheep bones. Bio-composites were doped with 1, 5, and 10 wt.% of expanded perlite and 5 wt.% of ZrO2–MgO-P2O5. The bio-composites were prepared by the cold isostatic pressing method (250 MPa) and sintered at 900°C for 1 h. In order to evaluate the characteristics of the bio-composites, microhardness, density, X-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Many studies have demonstrated that the addition of ceramics to SHA tends to enhance its mechanical performance and/or its biological properties [16]. For this purpose some ceramics such as niobium oxide [17], magnesium oxide [18], perlite [19] and bioactive glass [20] were used as reinforcement agent.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that the addition of ceramics to SHA tends to enhance its mechanical performance and/or its biological properties [16]. For this purpose some ceramics such as niobium oxide [17], magnesium oxide [18], perlite [19] and bioactive glass [20] were used as reinforcement agent.…”
Section: Introductionmentioning
confidence: 99%